Factors affecting the performance of professional nurses in Namibia - Magdalene H. Awases; Marthie C. Bezuidenhout; Janetta H. Roos (AOSIS, 2013)
Background: Professional nurses play a vital role in the provision of health care globally. The performance of health care workers, including professional nurses, link closely to the productivity and quality of care provision within health care organisations. It was important to identify factors influencing the performance of professional nurses if the quality of health care delivery was to improved. Objectives: The aim of the present study was to identify factors affecting the performance of professional nurses in Namibia. Method: A quantitative, descriptive survey was used to collect data by means of a questionnaire. A random sample of 180 professional nurses was selected from six hospitals in three regions of Namibia. Results: Factors affecting the performance of nurses negatively were identified such as: lack of recognition of employees who are performing well, quality performance outcomes and an absence of a formal performance appraisal system and poor working conditions. Various factors contribute to both the positive and negative performance of professional nurses in Namibia. Strategies were developed for addressing the negative factors that could positively affect the performance of professional nurses in Namibia. Conclusions: This study emphasises the importance of developing strategies to promote the performance of nurses; build knowledge and expertise; develop mechanisms for improving the performance of nurses; expand leadership and management capacity; and generate information and knowledge through research.